ANALYSING THE FACTORS AFFECTING TOURISM ENTREPRENEURSHIP AND THE DEVELOPMENT OF TOURISM-BASED SMES - Okadigwe John Chukwujekwu (Jurnal Ekonomi, Bisnis dan Pendidikan, 2024)
Tourism is one of the fastest-growing sectors in the global economy, contributing significantly to employment, economic growth, and cultural exchange. In many countries, tourism-based small and medium enterprises (SMEs) play an important role in driving local economies by creating jobs, fostering innovation, and enhancing the overall tourism experience. However, despite their potential, tourism-based SMEs often face numerous challenges that impede their growth and sustainability. This study examines the key factors influencing tourism entrepreneurship and the development of tourism-based small and medium enterprises (SMEs). A stratified random sampling technique selected 55 SMEs, including travel agencies, tour operators, and hotels. Data were collected via structured questionnaires and analyzed using descriptive statistics and regression analysis to identify factors impacting business growth. A pilot test ensured validity and reliability, with Cronbach’s alpha confirming internal consistency. Ethical standards were followed, and informed consent was obtained. Findings reveal that while government incentives, funding, and marketing strategies play crucial roles in supporting tourism entrepreneurship, the lack of adequate infrastructure and skilled labor remains significant barriers. The study suggests that a more supportive policy environment, enhanced funding mechanisms, and investments in infrastructure are essential to foster the growth and sustainability of tourism-based SMEs. Recommendations for improving the business environment for tourism entrepreneurship are provided, along with suggestions for future research in this area.